Institutional quality states EU-12 - Volejníková Jolana (Univerzita Pardubice, 2009)
The article deals with problems of institutions, ways of assessing and measuring their quality. At the theoretical level based on the text of a concept of institutional economics. In her conception of the institution are set out the rules and constraints that determine the evolution of society and economy of the country. In the article we first performed a comparative discussion of the methods of measurement and evaluation of the quality of institutions, available on latest stage of knowledge. In order to capture real trends in the institutional convergence of new Member States of the European Union (EU-12), we applied a statistical methodology for the World Bank's Governance Matters.
Keywords: institutions; institutional economics; European Union; quality of institutions; indices of institutional quality; methodology governance matters